Effect of Soya Bean Residue Supplemented with Kingzyme on Haematology and Serum Biochemistry of Broiler Finisher Chickens Diets. - Lawan, I.; Abdulazeez, H.; Yusuf, A.M.; Gazali, A.; Mohammed, A.A.; Bislava, M.B. (Nigerian Journal of Animal Science, 2026)
This study was carried out to investigate the potentials of soya bean residue (SBR) supplemented with Kingzyme® at finisher phase (4th – 8th weeks). A total of three hundred and sixty (360) day old Cobb 500 broiler chickens were randomly allocated to four (4) dietary treatments containing soya bean residue meal supplemented with Kingzyme® with different levels of supplementation designated as 0, 25, 30 and 35g. Each treatment was replicated thrice with thirty (30) birds per replica in completely randomize design (CRD). There were no significant (P>0.05) differences among treatment groups for all the haematological parameters except packed cell volume (PCV), haemoglobin (Hb), mean corpuscular volume (MCV) and mean corpuscular haemoglobin (MCH) which showed significant (P<0.05) differences but no definite trend in terms of Kingzyme® supplementation. However, in serum biochemical indices, there is no significant (P>0.05) differences among all the treatments group, total protein, albumin, globulin, urea, creatine, sodium (Na), potassium (K), aspartate aminotransferase (ASAT) and alanine aminotransferase (ALAT) while glucose, cholesterol, chloride, direct bilirubin, and conjugate bilirubin showed significant (P<0.05) differences among the treatment groups. Therefore, in conclusion, broiler chicken diets containing 18% soya bean residue supplemented with Kingzyme® can be used as protein source based on haemato-serum biochemical profile.